IMPACT OF GLOBALIZATION ON MACROECONOMIC POLICY - Clementina IVAN-UNGUREANU (Revista Romana de Economie, 2008)
Globalization – the growing integration of economies and societies around the world – has been one of the most hotly-debated topics in international economics over the past few years. Rapid growth and poverty reduction in some countries that were poor 20 years ago have been positive aspects of globalization. But globalization has also generated significant international opposition to concerns about increased inequality and environmental degradation. There are many definitions of globalization. One of them could be: globalization is an ecosystem in which economic potential is no longer defined or contained by political and geographic boundaries. Economic activity has no bounds in a globalized economy. A globalized world is one where goods, services, financial capital, machinery, money, workers and ideas migrate to wherever they are most valued and can work together most efficiently, flexibly and securely. Where does economic policy come into play in this world? This paper presents some aspects of globalization and the impact on the new strategy of macroeconomics policy.